Management control and effective implementation of the program budget in Cameroonian context - MBIDA, Joachim Achille Christel (Revue Internationale du Chercheur, 2024)
Management control in public administrations born from the switch to program budgeting and the need to effectively maneuver these organizations as well as propose corrective measures to remedy the dysfunctions of public management in order to improve its performance. The objective of this study is to understand why management control does not contribute effectively to the implementation of the program budget. To achieve this, we first carried out an exploratory study of thirty (30) players in the budget chain. This exploratory study then enabled us to carry out a survey of 114 actors in the performance chain in the central services of the 38 ministerial departments with 144 programs. The main results show that the switch to program budgeting does not yet give a preponderant place to management control in its effective implementation and partial mastery of management control tools does not contribute to the effective implementation of the budget. program.